Characteristics of the Physical Properties of Structurally Unstable Ground: Physical Properties of Frozen Ground - Tsytovich,N. A. (1966)
Frozen and permanently frozen ground also may be classified as structurally unstable because with an increase of their temperature to above zero the structure is radically modified, and also settling and sagging occur such as were observed in the earlier considered loessial soils when wetted and under a load. The freezing of the ground is accompanied by a considerable number of physicochemical and physicomechanical processes which have a considerable influence on their properties and structure. These processes are caused by the transition of the water in the soil pores, at the appropriate temperature, from a liquid to a solid state, that is, its freezing -- crystallization and the phenomena accompanying it. (Author) Trans. of mono. Mekhanika Gruntov (Soil Mechanics), Moscow, 1963 p90-103.